Tenosynovial Giant Cell Tumor pada Wanita Usia 32 Tahun : Sebuah Laporan Kasus - Ilham, Lalu Fahril; Lalu Fauzan Adi Yuliansyah (Faculty of Medicine, Universitas Mataram, 2024)
Tenosynovial giant cell tumors are a group of benign soft tissue tumors of synovial origin with characteristic histologic features. In general, based on the growth pattern, it can be divided into local and diffuse types, and based on the location of the growth, it can be divided into intra-articular and extra-articular. Local type tumors generally develop slowly, while diffuse type tumors develop more aggressively and often affect the patient's quality of life. Recent developments show that tenosynovial giant cell tumor is a clonal neoplastic tumor driven by overexpression of Colony Stimifying Factor 1 (CSF1) in the synovial area, thus forming a mass. In this case report, we report a case of localized tenosynovial giant cell tumor and recent developments regarding its pathogenesis.